2021
DOI: 10.3389/fonc.2021.676038
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Benefit Of Sentinel Lymph Nodes Biopsy Compared to Regional Lymph Node Dissection in Primary Vulvar Cancer Patients Without Distant Metastasis and Adjacent Organ Invasion: A Retrospective Population Study

Abstract: BackgroundThe safety and benefit of sentinel lymph node biopsy (SLNB) compared with regional lymph node dissection (RLND) and no lymph nodes removed (NA) in patients with vulvar squamous cell cancer (VSCC) was not well studied.MethodsA retrospective analysis on VSCC patients without distant metastasis and adjacent organ invasion from the Surveillance, Epidemiology, and End Results Program database between 2004 and 2016 was carried out. Within subgroups stratified by negative (LN−) or positive (LN+) regional ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…SLNB and lymphadenectomy have never been integrated as a predictor in nomograms for predicting the survival of patients with VSCC. However, the beneficial role of SLNB in improving survival has been proved in previous studies ( 17 19 ). The inclusion of SLNB in the model has improved the prediction accuracy considerably.…”
Section: Discussionmentioning
confidence: 93%
“…SLNB and lymphadenectomy have never been integrated as a predictor in nomograms for predicting the survival of patients with VSCC. However, the beneficial role of SLNB in improving survival has been proved in previous studies ( 17 19 ). The inclusion of SLNB in the model has improved the prediction accuracy considerably.…”
Section: Discussionmentioning
confidence: 93%
“…This could explain the low percentage of lymph-node metastasis in endometrial cancer: 10% for all-grade included endometrial carcinomas [ 11 ], 14% for the sentinel lymph node [ 12 ] or lymphadenectomy approaches [ 13 ], reaching almost 20% (most often micrometastases) even when introducing molecular techniques in the early-stage disease [ 14 ] and raising to 26% for high-grade cancers [ 15 ]. For vulvar cancer-draining lymph nodes, the metastatic ratio is slightly higher, 21–28% [ 16 ]. This could be in-line with the significantly higher PD-L1-positive cells in otherwise healthy vulvar cancer-draining LNs, compared to the endometrial cancer-draining LNs found here.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this technique has resulted in decreased postoperative morbidity without compromising detection of LN metastases [14][15][16]. Some studies were conducted with the aim of extending the indications for the sentinel lymph node biopsy, which could be reached more easily having in hand an adequate screening tool in the preoperative phase [17][18][19].…”
Section: Introductionmentioning
confidence: 99%